Composites Nafion-titania membranes for Polymer Electrolyte Fuel Cell (PEFC) applications at low relative humidity levels: Chemical physical properties and electrochemical performance. (December 2016) - Saccà, Ada; Carbone, Alessandra; Gatto, Irene; Pedicini, Rolando; Freni, Angelo; Patti, Assunta; Passalacqua, Enza
Abstract: The incorporation of inorganic compounds into the polymeric Nafion matrix represents a possible solution to improve the mechanical characteristics of the polymeric membranes when drastic operative conditions (higher temperatures and/or lower relative humidity levels) are adopted in a Polymer Electrolyte Fuel Cell (PEFC). On the basis of previous investigations, different commercial anatase titanium oxide (TiO2 ) loadings were used to prepare composite membranes with the aim of reducing the humidification levels for a PEFC stack. Membranes with three different TiO2 contents (5, 10, 15 wt.%) were cast and characterized in terms of chemical-physical and electrochemical behaviour. The influence of filler was highlighted resulting in a swelling reduction of the composite membranes if compared to a pristine recast Nafion membrane cast with the same method and used as a reference. A good proton conductivity was observed for all composite Nafion-titania (N-TiO2) membranes with values ranging 1.3–1.9·10 −2  S cm −1 at 60 °C and 50%RH against a value of 1.5·10 −2  S cm −1 related to the reference membrane. The composite membrane containing a 10 wt.% of TiO2 has shown an improved performance respect to the reference membrane, especially at low levels of humidification and a higher stability during the accelerated stress test (AST) carried out in drastic conditions (60 °C and 50%RH), probably due to the filler capability to reduce the swelling and give stiffness to the polymeric matrix.